Developing a novel multi-epitope vaccine against Dengue virus targeting the Envelope protein using an Immunoinformatics approach - NASIFUZZAMAN, S M (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology 2021.